Formal Modeling and Analysis of an Audio/Video Protocol: An Industrial Case Study Using UPPAAL - Havelund, Klaus; Skou, Arne; Larsen, Kim G.; Lund, Kristian (BRICS Report Series, 1997)
A formal and automatic verification of a real-life protocol is presented. The protocol, about 2800 lines of assembler code, has been used in products from the audio/video company Bang & Olufsen throughout more than a decade, and its purpose is to control the transmission of messages between audio/video components over a single bus. Such communications may collide, and one essential purpose of the protocol is to detect such collisions. The functioning is highly dependent on real-time considerations. Though the protocol was known to be faulty in that messages were lost occasionally, the protocol was too complicated in order for Bang & Olufsen to locate the bug using normal testing. However, using the real-time verification tool UPPAAL, an error trace was automatically generated, which caused the detection of “the error” in the implementation. The error was corrected and the correction was automatically proven correct, again using UPPAAL. A future, and more automated, version of the protocol, where this error is fatal, will incorporate the correction. Hence, this work is an elegant demonstration of how model checking has had an impact on practical software development. The effort of modeling this protocol has in addition generated a number of suggestions for enriching the UPPAAL language. Hence, it’s also an excellent example of the reverse impact.